Non-small Cell Lung Cancer Cell Line PC-9 Drug-resistant Mutant Cell Line Establishment and Validation of Their Sensitivity to EGFR Inhibitors - Tao HU; Yang LOU; Mingbo SU (Chinese Journal of Lung Cancer)
Background and objective Mutations in the structural domain of the epidermal growth factor receptor (EGFR) kinase represent a critical pathogenetic factor in non-small cell lung cancer (NSCLC). Small-molecule EGFR-tyrosine kinase inhibitors (TKIs) serve as first-line therapeutic agents for the treatment of EGFR-mutated NSCLC. But the resistance mutations of EGFR restrict the clinical application of EGFR-TKIs. In this study, we constructed a clinically relevant PC-9 EGFRD19/T790M/C797S cellular model featuring the mutation type within the EGFRD19/T790M/C797S. This model aims to investigate the inhibitory effects of small-molecule EGFR-TKIs and to provide a cellular platform for developing a new generation of innovative drugs that target resistance associated with EGFR mutations. Methods Clustered regularly interspaced short palindromic repeats/CRISPR-associated nuclease 9 (CRISPR/Cas9) technology was employed to knock in the EGFRT790M/C797S mutant fragment into NSCLC PC-9 cells, originally harboring the EGFRD19 mutation, to generate the PC-9 EGFRD19/T790M/C797S cell model. This model, with the EGFRD19/T790M/C797S mutant, was used to investigate the inhibitory effects of EGFR-TKIs on cell proliferation through MTS assay. Additionally, Western blot analysis was conducted to assess the regulation of EGFR protein expression and the phosphorylation levels of downstream signaling molecules, including protein kinase B (AKT) and mitogen-activated protein kinase (MAPK). Results PC-9 EGFRD19/T790M/C797S cells, with the EGFRD19/T790M/C797S mutation, were successfully generated using CRISPR/Cas9 technology. In terms of proliferation inhibition, the marketed first-, second-, and third-generation EGFR-TKIs that were ineffective against the EGFRD19/T790M/C797S mutation showed weak proliferation inhibitory activity against this cell line, and the proliferation inhibition (half maximal inhibitory concentration, IC50)>1000 nmol/L; in contrast, the fourth-generation EGFR-TKIs in development, which have better efficacy against the EGFRD19/T790M/C797S mutation, showed strong proliferation inhibition in this cell model. On mechanistic validation, the first-, second-, and third-generation EGFR-TKIs had weak inhibitory activity on the phosphorylation of EGFR and the downstream AKT/MAPK signaling pathway in this cell line, whereas the fourth generation of EGFR-TKIs under development significantly inhibited the phosphorylation of EGFR and the downstream AKT/MAPK signaling pathway in this cell line. Conclusion Using CRISPR/Cas9 technology, the EGFRT790M/C797S mutant fragment was successfully knocked into PC-9 cells to create cell lines harboring the EGFRD19/T790M/C797S mutation. The study demonstrated that the EGFR-TKIs showed different sensitivities to whether the EGFRD19/T790M/C797S mutation was effective or not and different inhibitory effects on the phosphorylation of EGFR and downstream pathways, which demonstrated that this cell line depended on the activation of the EGFRD19/T790M/C797S mutation and EGFR/AKT/MAPK signaling pathway for proliferation. This study provides a clinically relevant cellular evaluation and mechanism validation system for the development of a new generation of innovative drugs targeting EGFR mutation resistance.